Land Use in the Border, Eastern Cape Province - Board, Christopher (ERDKUNDE, 1960)
The land use survey, conducted from 1955 to 1958, was part of a comprehensive regional survey of the Border by Rhodes University in the Union of South Africa. It was supported and funded by a number of government agencies. The field survey, conducted with the aid of large-scale maps and aerial photographs, covered 1547 square miles in the area of the port city of East London on the southeast coast of the Union. A twelve-color land use map using the International Geographical Union classification system was drawn. The Border takes its name from the fact that it was once a border zone between the settlement areas of Europeans and Bantu tribes. Today it is a mixed settlement area with a large number of different types of land use. In order to show the differentiation of the landscape, three areas with almost the same natural features but different types of land use are examined and presented here in detail. 1. the arable highland of the natives: This is the settlement area of the Bantus, but in which the traditional land use methods underwent a change as a result of the prevailing population pressure. A communal grazing economy has been replaced by a partial self-sufficiency agriculture based on maize cultivation and the income of population segments temporarily employed in industry. Official land-use planning aims to move at least part of the population entirely to mixed (i.e., crop-livestock) agriculture. 2 The pineapple zone: The cultivation of a single fruit for export gives the land use of this area its dominant character. Large capital investments and relatively low productivity make this expensive type of farming very dependent on price movements in the world market. Although most of the arable land is devoted to the production of this one commercial crop on white-owned farms, a larger percentage of the grassland is grazed by the cattle of Bantu agricultural workers. 3. German Settlements: Scattered parcels of common land and small ownerships were transferred to military settlers and farmers in 1858. The mixed agriculture practiced on them is just sufficient for subsistence, but provides little additional income beyond that. Unfavorable natural conditions, lack of capital, and the legalities of land ownership prevent consolidation into larger and more viable farms.